Análise da variação anatômica da artéria hepática no transplante de fígado - Silva, Alexandre Cerqueira da (2004)
Since 1963, liver transplantation developed from an experimental procedure until to be implemented in the early 80 s as medical therapy for liver diseases, when the organ substitution is indicated. The study of the hepatic artery started at XVIII century, but only at the last three decades, this subject was really emphasized, because of the realization of liver transplantation and other more complex modalities of this procedure as living and split liver transplantation for two recipients. From March 2002 to March 2005 eighty cadaveric donors were evaluated according to the types of hepatic artery anatomy. The habitual anatomy was found in 67,5% with 32,5% being abnormal already described on literature. From 80 recipients, two have presented arterial thrombosis ( 2,5%). There was no correlation between arterial variation and the number of anastomosis with the index of arterial thrombosis. The study of the arterial vascularization of the liver is useful in hepatic-biliary pancreatic surgery; it is fundamental to prevent complications at liver transplantation with graft originating from donors with cerebral death and crucial when more complex procedures are done as living-donor liver transplantation and split liver transplantation.